A pitfall of thoracoscopic thymectomy: a case with intraoperative and postoperative complications - Motoki Yano; Hiroki Numanami; Masayuki Yamaji; Rumiko Taguchi; Chihiro Furuta; Masayuki Haniuda (Surgical Case Reports)
Abstract We have reported the usefulness of the subxiphoid approach in thymectomy. However, such a new operation method may have unknown complications that rarely occur. Surgeons cannot completely avoid intraoperative and postoperative complications. We report a case of intraoperative injury of the orifice of the left internal thoracic vein flowing to the left brachiocephalic vein and postoperative pericarditis following video-assisted thoracic surgery (VATS) thymectomy. The innominate vein has been considered to be the vessel that is most frequently injured especially at the orifice of the thymic veins. We also suggest that the orifice of the left internal thoracic vein is the second dangerous location that requires special care. In addition, postoperative pericarditis occurred in this patient. Pericardial drainage was necessary. No additional complications have been found in the 9 months since the operation. Though VATS thymectomy using the subxiphoid approach is a safe and less-invasive operation, intraoperative and postoperative complications were possible to be occurred.